2015
DOI: 10.1186/s12913-015-0921-1
|View full text |Cite
|
Sign up to set email alerts
|

A brief report on the development of a theoretically-grounded intervention to promote patient autonomy and self-management of physiotherapy patients: face validity and feasibility of implementation

Abstract: Background: Clinical practice guidelines for the treatment of low back pain suggest the inclusion of a biopsychosocial approach in which patient self-management is prioritized. While many physiotherapists recognise the importance of evidence-based practice, there is an evidence practice gap that may in part be due to the fact that promoting self-management necessitates change in clinical behaviours. Evidence suggests that a patient's motivation and maintenance of self-management behaviours can be positively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Specifically, within the SOLAS intervention, this criteria should highlight how these BCTs should be fully delivered using a SDT-based communication style, as a recent review found that a person-centred manner of BCT delivery explained all of the between-study variations in long-term behaviour maintenance, thus supporting its inclusion for effective interventions (Samdal et al, 2017). Furthermore, as fidelity guidelines suggest that providers be monitored during delivery (Bellg et al, 2004;Borelli, 2011), individualized feedback could be provided to those that need it (Fixsen, Blase, Metz, & VanDyke, 2013;Matthews et al, 2015). Therefore, individual 'booster' or 'coaching' sessions could be considered within future training programmes to further enhance provider delivery.…”
Section: The Effectiveness Of Bct Training Within the Solas Interventionmentioning
confidence: 99%
“…Specifically, within the SOLAS intervention, this criteria should highlight how these BCTs should be fully delivered using a SDT-based communication style, as a recent review found that a person-centred manner of BCT delivery explained all of the between-study variations in long-term behaviour maintenance, thus supporting its inclusion for effective interventions (Samdal et al, 2017). Furthermore, as fidelity guidelines suggest that providers be monitored during delivery (Bellg et al, 2004;Borelli, 2011), individualized feedback could be provided to those that need it (Fixsen, Blase, Metz, & VanDyke, 2013;Matthews et al, 2015). Therefore, individual 'booster' or 'coaching' sessions could be considered within future training programmes to further enhance provider delivery.…”
Section: The Effectiveness Of Bct Training Within the Solas Interventionmentioning
confidence: 99%
“…In addition to the video-taped sessions used in the pilot study, the clinicians also had the opportunity to work on phrasing and delivery through active case scenarios. Use of mixed training methods (didactic and interactive) have shown to be more effective than a single method alone (Forsetlund et al, 2009; Matthews et al, 2015). Throughout the training sessions, the clinicians were encouraged to begin trying the techniques.…”
Section: Methodsmentioning
confidence: 99%
“…SDT-based interventions typically include a series of communication strategies targeting a patient's basic needs (e.g. asking open-ended questions, paraphrasing and gauging the patient's readiness to accept advice); we have previously demonstrated that this type of training can increase physiotherapists' autonomy supportive behaviour in their clinical interactions with patients [5].…”
Section: Self-determination Theory and Patient Adherence To Treatmentmentioning
confidence: 96%